Medicinal Plants from Near East for Cancer Therapy - Abu-Darwish, Mohammad S.; Efferth, Thomas (Frontiers in Pharmacology, 2018)
Background: Cancer is one of the major problems affecting public health worldwide. As other cultures, the populations of the Near East rely on medicinal herbs and their preparations to fight cancer. Methods: We compiled data derived from historical ethnopharmacological information as well as in vitro and in vivo results and clinical ﬁndings extracted from different literature databases including (PubMed, Scopus, Web of Science and Google Scholar) during the past two decades. Results: In this survey, we analyzed the huge amount of data available on anticancer ethnopharmacological sources used in the Near East. Medicinal herbs are the most dominant ethnopharmacological formula used among cancer’s patients in the Near East. The data obtained highlight for the first time the most commonly used medicinal plants in the Near East area for cancer treatment illustrating their importance as natural anticancer agents. The literature survey reveals that various Arum species, various Artemisia species, Calotropis procera., Citrullus colocynthis, Nigella sativa, Pulicaria crispa, various Urtica species, Withania somnifera.and others belong to the most frequently used plants among cancer patients in the Near East countries. Molecular modes of action that have been investigated for plant extracts and isolated compounds from Near East include cell cycle arrest and apoptosis induction with participation of the major player in these processes such as p53 and p21, Bcl-2, Bax, cytochrome C release, PARP cleavage, activation of caspases etc. Conclusions: The ethnopharmacology of the Near East was influenced by Arabic and Islamic medicine and might be promising for developing new natural and safe anticancer agents. Further research is required to elucidate their cellular and molecular mechanisms and to estimate their clinical activity.